WOMEN'S SOLIDARITY AND STRATEGIC LEADERSHIP: AN EMPOWERMENT MODEL FOR HALAL MENTORS AT LP3H UIN SUNAN KALIJAGA - Humam, Abdul Wadud Kasful; Alfi, Ahmad Musonnif (Kafa`ah: Journal of Gender Studies, 2025)
This study aims to analyze the practice of empowering women who work as halal assistants at LP3H UIN Sunan Kalijaga. Women's participation and gender equality that places women in a position equal to men are an important part of the success of the Sustainable Development Goals (SDGs) program including women's empowerment and economic independence. The method used in this research is field research (faild research) with data collection techniques through observation, interviews and documentation about halal assistance and halal women assistants at LP3H UIN Sunan Kalijaga. The results of this study indicate that in the midst of a patriarchal culture that is still rooted in Indonesian society, women who work as halal assistants are able to survive and there are even practices of women's empowerment, this is indicated by cooperation, collaboration, and even mutual support between female assistants. The formation of an organization/community as a forum for halal assistants is very influential on the productivity of assistance carried out by women. In addition, the factor of strategic positions filled by women both as chairman / management of communities such as Pumikop and Forkom (Communication Forum) UMKM makes women more active and productive in providing assistance to business actors